INCREASING AWARENESS CAPACITY OF DISASTER POTENTIAL AS A SUPPORT TO ACHIEVE SUSTAINABLE DEVELOPMENT GOAL (SDG) 13 IN LAMPUNG PROVINCE - Indra Jaya Wiranata; Khairunnisa Simbolon (Universitas Potensi Utama, 2021)
Global policies on the Sustainable Development Goals (SDGs) address several aspects of environmental life and climate change. There are still challenges that many regions do not pursue the achievement of sustainable development goals which means that SDGs cannot simply and automatically be achieved in several regions due to different contexts and different geographic backgrounds. Extreme climate change can cause natural disasters that have the potential to cause losses and even claim victims. Thus, Lampung, which is a disaster-prone area, is interesting to be studied whether the government and the community's efforts to realize potential disasters have been accomplished properly. This research explains the efforts that have been and need to be done by Lampung Province in responding to potential disasters through a policy brief in order to motivate the government to pay more attention to climate change and natural disasters. This research is a type of qualitative research with primary data that will be taken by using interview techniques and literature review. The survey was conducted by random sampling the people of Lampung regarding the level of awareness of potential disasters. The data will also be obtained by using Google Trend. The results of this research indicate that the efforts of the Lampung Provincial Government such as mitigation, emergency response, reconstruction, rehabilitation, disaster risk assessments, and support from the epistemic community.